Case Study of a Hybrid (Wind and Solar) Power Plant - Sunil M Jaralikar; Mangalpady Aruna (Universitas Ahmad Dahlan, 2011)
The paper highlights the urgency of utilizing and promoting use of non conventional sources, particularly the wind and solar energy, so as to control the environmental pollution, such as ozone layer depletion, deforestation, loss of biodiversity, global warming etc. As a case study, the various performance factors of a 10 kW hybrid (wind and solar) power plant, which is having 60:40 power generation share of wind power to solar power were analysed. The study shows that there is mismatch between the designed and actual plant load factor (PLF), as well as the power generation share of the wind and solar power plant. It was also found that the plant utilization factor (PUF) was poor and that there is very less scope for installation of solar tracking system. Based on the detailed analysis of obtained results, certain recommendations were made for streamlining and optimizing the power generation capacity, and also for better utilization of generated power.